Influencia de la adición de bacterias lácticas en el cultivo del rodaballo (Scophthalmus maximus L.) - García-de-la-Banda, Inés; Chereguini-Fernández-Maquieira; María del Olvido; Rasines, Inmaculada (1992)
Sí